The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.taap.2008.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite-induced mitotic death involves stress response and is independent of tubulin polymerization

Abstract: Arsenite, a known mitotic disruptor, causes cell cycle arrest and cell death at anaphase. The mechanism causing mitotic arrest is highly disputed. We compared arsenite to the spindle poisons nocodazole and paclitaxel. Immunofluorescence analysis of α-tubulin in interphase cells demonstrated that, while nocodazole and paclitaxel disrupt microtubule polymerization through destabilization and hyperpolymerization, respectively, microtubules in arsenite-treated cells remain comparable to untreated cells even at sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
3
28
1
Order By: Relevance
“…The induction of lagging chromosomes [14,16] suggests a disruption of microtubule assembly dynamics; however, two more recent studies suggest that arsenic does not affect spindle formation [7,21]. The second possibility is effects on the SAC, arsenic-induced mitotic cell death requires the activation of the SAC indicated by the activation and proper localization of BubR1, Mad2 and Cdc27 and the stabilization of securin and cyclin B, [7,17,18].…”
Section: Carcinogenic Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of lagging chromosomes [14,16] suggests a disruption of microtubule assembly dynamics; however, two more recent studies suggest that arsenic does not affect spindle formation [7,21]. The second possibility is effects on the SAC, arsenic-induced mitotic cell death requires the activation of the SAC indicated by the activation and proper localization of BubR1, Mad2 and Cdc27 and the stabilization of securin and cyclin B, [7,17,18].…”
Section: Carcinogenic Metalsmentioning
confidence: 99%
“…Centrosome amplification is induced by arsenic treatment, and it has been detected indirectly through the formation of multi polar spindles and directly by immunoflourescent staining of centrosomes [18,20,21,23,24,25]. Arsenite-induced centrosome amplification does not require dysfunctional p53, but the loss of p53 results in a significant increase in centrosome amplification which would lead inevitably to further instability [21,24]. Co-treatment with other carcinogens, such as nicotine-derived nitrosamine ketone (NNK) which reduces p53 in the nucleus, synergistically increases centrosome amplification [25].…”
Section: Carcinogenic Metalsmentioning
confidence: 99%
“…In HeLa cells, the microtubule poison nocodazole partially blocks accumulation of condensed chromatin within surface blebs, and confocal imaging revealed that microtubules associate closely with chromatin within late apoptotic surface blebs [19,20]. However, Taylor et al [21] reported that arsenite-induced mitotic death was independent of tubulin polymerization. Beside arsenic, a number of anti-cancer drugs produce proapoptotic effects by their microtubule-toxicity.…”
Section: Jwa Regulates Tubulin Polymerization and Cell Apoptosis Via P38mentioning
confidence: 99%
“…Arsenic-induced centrosome amplification occurs in mitotic cells but does not appear to occur in interphase cells [7] and is associated with a prolonged mitotic arrest [57]. Arsenic-induced mitotic arrest and subsequent centrosome amplification and multipolar spindle formation requires the spindle assembly checkpoint as data show that inhibition of BubR1 and Mad2 attenuate arsenic-induced centrosome amplification [7,8]. In addition, data show that the amplified centrosomes caused by arsenic contain either abnormal centriole numbers or no centrioles at all, suggesting centrosome fragmentation and/or overexpression of pericentriolar proteins are involved in the underlying mechanism [7].…”
Section: Metal-induced Centrosome Amplificationmentioning
confidence: 99%